School Response to Self-Injury: Concerns of Mental Health Staff and Parents - Kelada, L.; Hasking, Penelope; Melvin, G. (2017)
Nonsuicidal self-injury (NSSI) among adolescents poses a significant problem for schools, adolescents, and their families. However, appropriate guidelines for addressing NSSI, including when to disclose the behavior to parents, are currently lacking. The present study aimed to understand how school mental health staff and parents of secondary school students view NSSI to determine how parent-school communication about NSSI, and responses to NSSI, can be improved. Nineteen school mental health staff participated in interviews and 10 parents of adolescents with a history of NSSI completed open-ended questionnaire items. Staff identified that sector-wide NSSI policy and education for teachers and principals would help them feel more supported and improve consistency in addressing NSSI between and within schools. In contrast, parents wanted more support directed at them rather than solely their adolescent. Implications for policy and parental support provided by the school are discussed. (PsycINFO Database Record